Road Safety and Sustainability: A Comparison of Country Rankings - Csaba Koren; Ziyad N. Aldoski (Chemical Engineering Transactions, 2023)
Road traffic deaths are a crucial problem in the world. At the same time, sustainability is a global issue. Numerous publications are dealing with road safety and sustainability separately as a basis for country rankings, but if you are searching for “road safety and sustainability”, no relevant results are found. The research question of this paper is: How is the safety performance of countries with good sustainability ranks? Vice versa: are countries with lower sustainability ranks more dangerous in traffic? To answer these questions, international sustainability and safety ranking scales were compared using Spearman correlation coefficients. The key finding of the paper is that there is a strong correlation between sustainability and the safety ranking of countries. However, there are some exceptions, countries with significantly different sustainability and safety performances.